Re-citation and resuscitation from the archives of Arab revolution. (11th March 2019) - Dickinson, Kay
Abstract: From graffiti to festival films, revolutionary expression aligned to what is popularly labelled 'the Arab Spring' has made regular and sustained reference to film and other media from Egypt's past. One moment in particular dominates, that of the mid to late 1960s, when explicitly anticolonial and revolutionary media was produced and widely disseminated across the Arab world, backed by largely state-run industries. Drawing on postcolonial Arab historiography and committed poetry, this essay engages with how re-citations and resuscitations of cinema and music from this period inspired and bedded down revolutionary principles. It then examines how contemporary quotations from this archive explore the corruption and destruction of nationalized (media) industries in order to dialectically question broader practices of labour casualization and privatization across the region.